Law of value based on contact and representation. An ethnographic study - Rauszer, Michał (Studia Etnologiczne i Antropologiczne, 2017)
The aim of this text is to depict the evolution of change in representations of labor and value in a neoliberal society. This evolution is shown through ethnographical studies of small companies in the Upper Silesia as well as the work performed in such companies. The study argues that due to the influence of neoliberał ideology, the social functioning of labor and value has evolved from the class paradigm in the industrial society to a discontinuous structure of the set in the contemporary society. Labor has also changed its measurable representative features. For example, labor is no longer perceived through the lens of worktime or effort, but rather through the lens of value. The text constitutes an analysis of the changes in the labor and value structure and how this structure is perceived in a neoliberal society.